Characterization of mechanical properties of polyurea - You, Mei Yu (Nanyang Technological University, 2023)
The use of polyurea in the field of protection and armour shows great promise, showing high elongation, elasticity, tensile strength and hardness. Ceramic armour reinforced with polyurea show an increase mass effiency compared to non-reinforced polyurea. This interlayer of polyurea will be of an optimized thickness of about 2 mm. However, most research on the curing and characteration of polyurea are done on spray coating polyurea, and the effects of various curing factors on thick layers are not well understood. This paper investigates the effects of differing curing properties on the mechanical properties of the polyurea in thickness from 2mm. The effects to be investigated are ratio of isocyanate and polyamine, temperature, curing time and humidity. The polyurea was successfully synthesized with Isonate-143LP Modified MDI and oligomeric diamine (VERSALINK P1000). The polyureas were allowed to cure until different factors and conditions for up to 5 days. Quasi-static tensile test was conducted on the polyurea samples cut into ASTM-D638 standard. The test reveals that there was a significant increase in tensile strength in the 3:7 ratio compared to the 4:6 ratio polyurea. After curing for 12 days, the 3:7 ratio samples demonstrated an average tensile strength of 32 MPa, compared to 27MPa of the 4:6 ratio samples. Additionally, the strain was also significantly higher, with 300% strain on the 3:7 ratio samples compared to 175% strain on the 4:6 ratio samples. The tests also demonstrates a general trend of increasing tensile strength and increasing strain with longer duration of curing for the temperature range of 40℃ to 100℃ at 20℃ intervals. The temperature comparisons show that curing at 40℃ produces polyurea samples with high tensile strength and high strain, showing an average range of 47-49 MPa for tensile strength, with a range of 465% - 472% strain. While the higher temperature 100℃ also produces high tensile strength of a range of 43-48 MPa, the strain is greatly reduced to 378-395%. Temperatures higher that 100℃ produces polyurea samples with defects of air bubbles, compromising the mechanical properties of the polyurea and causing premature failure.